Democracy, Human Development, Income Distribution and Regional Economic Performance: A Panel Data Analysis of 34 Provinces in Indonesia - Sijabat, Rosdiana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Many studies have concluded that the condition of democracy, the level of human development, and income distribution have associations with economic performance as measured by economic growth. However, the results of empirical studies on the relationship between these variables remain inconclusive. The objective of this study is to examine the effects of democracy, human development, and income distribution on economic growth in Indonesia's 34 provinces between 2012 and 2020. This study uses panel data analysis conducted using a Fixed Effect Model (FEM) approach. The findings reveal that human development (as measured using the Human Development Index) significantly affects gross regional domestic product (GRDP) growth. Meanwhile, democracy (measured through the Democracy Index) and income inequality (measured using the Gini Coefficient) are not statistically affected by GRDP growth. The findings have policy implications for provincial governments in developing policies that encourage strategic investment in human resources. The provincial government can implement policies that enhance the association between human development and economic development. Such policies are essential due to the strong relationship between human development and regional economic growth, necessitating an integrated strategy to enhance human and economic development.